East and South-East Asia international relations and security perspectives - Tan, Andrew Tian Huat. (London : Routledge, 2013)
Prentation de l'iteur :'Provides an overview of East and South-East Asia's international relations, security perspectives, foreign and defence policies, and regional non-traditional security issues, including globalization, transnational health challenges, population growth and the environment.'
The rise of East and South-East Asia : challenges and security perspectives / Andrew T. H. Tan -- China's international relations and security perspectives / Jing Huang -- The limitations of deterrence : China's response to military balancing in the western Pacific / Jonathan Holslag -- The'China threat' conundrum in East and South-East Asia / Andrew T.H. Tan -- The false promise of economic interdependence : Chinese foreign policy in North-East Asia / Nicholas Khoo -- China's approach to North Korea : seeking stability and influence amid changing circumstances and conflicting imperatives / Robert G. Sutter -- China-Japan relations : competition amidst interdependence / Paul J. Smith -- China and Taiwan relations : challenges and prospects / Sheryn Lee -- China-South-East Asian relations since the Cold War / Ja Ian Chong -- Japan : (more or less) normal military power / Axel Berkofsky -- The future of the US-Japan alliance / Christopher W. Hughes -- North Korea's security perspectives / Hazel Smith -- North Korea's impact on North-East Asian security / Nolan Theisen -- Inter-Korean relations and the challenge of North-East Asian regional security / John Swenson-Wright -- South-East Asia's international relations and security perspectives / Jurgen Haacke -- The USA's relations with East and South-East asia / Mark Beeson -- Globalization and East and South-East Asia / Alistair D.B. Cook -- Environmental challenges in East and South-East Asia / J. Jackson Ewing -- Environmental challenges in China / Graeme Lang -- Future pandemics : transnational health challenges in East and South-East Asia / Allen Yu-Hung Lai, Adam Kamradt-Scott and Richard Coker -- Transnational organized crime in East and South-East Asia / Roderic Broadhurst and Vy Kim Le -- Terrorism in South-East Asia after 9-11 / Andrew T.H. Tan -- Maritime security in East and South-East Asia / Justin V. Hastings -- Demographic ageing in China : economic problem or social opportunity? / Phil Mullan and Bill Durodie -- Japan's demographic crisis : security implications and obstacles to resolving an issue symptomatic of national decline / Brad Williams -- The future of regionalism in East and South-East Asia / Christopher B. Roberts.
Includes index and bibliography.
Keywords: Security, International -- East Asia; Security, International -- Southeast Asia; East Asia -- Foreign relations; Southeast Asia -- Foreign relations